Obstetrical and perinatal complications in women with body weight deficiency - L. P. Shelestova; R. S. Allahverdiev; V. G. Syusyuka (Zaporozhye State Medical University, 2016)
The knowledge about the impact of body weight deficiency during pregnancy, childbirth and state of newborns is very important for obstetricians. Aim. To estimate pregnancy course, childbirth and conditions of newborn in women with body weight deficiency. Methods and results. The pregnancy and childbirth in 41 women with body weight deficiency and 35 healthy pregnant women with normal body weight has been analyzed. Definition of body weight deficiency has been carried out in accordance with WHO recommendations (1997) on the body mass index. Women with body weight deficiency are characterized by high rate of threatened abortion, early toxicosis, anemia, placental dysfunction, fetal growth retardation, bones and ligaments diseases. The parturition is usually characterized by untimely rupture of membranes and anomalies of labor activity. Perinatal consequences are characterized by high rate of intrauterine development and newborn baby with low birth weight. The detected complications during pregnancy and childbirth in women with body weight deficiency, and their effect on the fetus indicate the need for medical interventions aimed at correcting these complications. Conclusions. The identified obstetric and perinatal complications in women with body weight deficiency, indicate the need for medical measures aimed at the prevention and reduction of complications during pregnancy and childbirth, which will also positively affect the fetal condition.